AB0274 THE PREDICTIVE VALUE OF RHEUMATOID FACTOR, ANTI-CITRULLINATED PROTEIN ANTIBODIES, ANTI-CARBAMYLATED PROTEIN: ANTIBODIES AND ANTI-PEPTIDYL ARGININE DEIMINASE TYPE-3 ANTIBODIES, ALONE OR IN COMBINATION, ON RADIOGRAPHIC DAMAGE IN RHEUMATOID ARTHRITIS. (June 2019) - Nissen, Michael; Lamacchia, Céline; Courvoisier, Delphine; Jarlborg, Matthias; Roux-Lombard, Pascale; Moeller, Burkhard; Ciurea, Adrian; Finckh, Axel; Bentow, Chelsea; Martinez-Prat, Laura; Mahler, Michael; Gabay, Cem
Abstract : Background: Autoantibodies such as anti-citrullinated protein antibodies (ACPA), anti-carbamylated protein antibodies (CarP) and anti-peptidyl arginine deiminase 4 (PAD4) antibodies have been associated with disease severity and radiographic progression in rheumatoid arthritis (RA). However, very little is known about the anti-PAD 3 (PAD3) antibodies and of the added value of combining multiple autoantibodies to predict radiographic damage. Objectives: To investigate the capability of rheumatoid factor (RF), ACPA, anti-CarP and anti-PAD3 antibodies to predict radiographic damage in RA, both individually and in combination. Methods: We performed a nested cohort study within the « Swiss Clinical Quality Management » (SCQM) RA registry. Biobank samples were tested for RF [QUANTA Lite (QL), IgM and IgA], ACPA IgG [QL CCP3 and QUANTA Flash (QF) CCP3], anti-CarP IgG [using carbamylated fetal calf serum as antigen by prototype ELISA, research use only (RUO)] and anti-PAD3 IgG [QF PAD3, RUO] (all methods Inova Diagnostics). Outcome: radiographic damage assessed with a validated scoring method, the Ratingen (Rau) score. We examined the association of each autoantibody both separately and combined, with radiographic damage at baseline and over time with linear mixed-effects models. Multivariable analyses were corrected for age, sex, smoking status, disease duration, disease activity (DAS28), number of prior biologics and calendar year of biosampling. Results: A total of 851 RA patients were included with a median of 4 Ratingen scores per patient. Autoantibodies were positive in the following proportion of patients: RF IgM 66.3%, RF IgA 56.9%, QL CCP3 63.8%, QF CCP3 63.3%, anti-PAD3 10.7% and anti-CarP 22.4%. Significantly higher baseline Ratingen scores were associated with the presence of RF (IgM and IgA) and anti-CCP3 (QL and QF) and greater progression over time with RF IgM and QL CCP3 IgG ( p =0.01 and p =0.04 respectively). Patients' positive for anti-PAD3 demonstrated higher mean baseline Ratingen scores compared with anti-PAD3 negative patients (14.9 vs. 8.8 respectively) which was significant in both univariable (Figure) and multivariable analyses ( p =0.0002 and p =0.02 respectively). In the QL CCP3 negative subgroup (n= 308), baseline Ratingen scores were significantly higher in anti-PAD3 positive patients ( p =0.01).There were no significant differences with regards to anti-CarP, either in the whole population or in the seronegative cohorts. The presence of multiple autoantibodies was associated with higher baseline Ratingen scores, particularly the combination of RF IgM, RF IgA, QL CCP3, and anti-PAD3, with a baseline Ratingen score of 16.1 ( p <0.00001 compared to those with no autoantibodies). The presence of at least 3 of the following autoantibodies: RF IgM, QL CCP3, anti-CarP and anti-PAD3, was associated with significantly greater radiographic progression over 10 years (Figure) than if these autoantibodies were absent ( p =0.03). Conclusion: The presence of anti-PAD3 antibodies was associated with significantly higher scores of radiographic damage at baseline, in both the overall population and in the subgroup of ACPA-negative patients. Combinations of autoantibodies (including anti-CarP and anti-PAD3) predicted both higher baseline radiographic damage and greater radiographic progression over time. Disclosure of Interests: Michael Nissen Consultant for: AbbVie, Lilly, Novartis, and Pfizer, Céline Lamacchia: None declared, Delphine Courvoisier Grant/research support from: has received an unrestricted grant from MSD for this study, Consultant for: has received consulting fees from BMS, Pfizer, AB2 Bio and Janssen., Paid instructor for: Janssen, Matthias Jarlborg: None declared, Pascale Roux-Lombard: None declared, Burkhard Moeller Consultant for: Swissmedic Human Medicines Expert Committee Member (regulatory agency), Adrian Ciurea Consultant for: AbbVie, Celgene, Janssen-Cilag, MSD, Eli Lilly, Novartis, Pfizer, UCB, Speakers bureau: Abbvie, Celgene, Janssen-Cilag, MSD, Eli Lilly, Novartis, Pfizer, UCB, Axel Finckh Grant/research support from: Bristol-Myers Squibb, Pfizer Inc, Consultant for: AbbVie, A2Bio, Bristol-Myers Squibb, MSD, Roche, Pfizer Inc, and UCB, Chelsea Bentow Employee of: INOVA Diagnostics, Laura Martinez-Prat Employee of: Inova Diagnostics (Not pharmaceutical, diagnostics company), Michael Mahler Employee of: Inova Diagnostics (Not pharmaceutical, diagnostics company), Cem Gabay Grant/research support from: Roche, Pfizer, AB2 Bio Ltd, Consultant for: Roche, Pfizer, Lilly, AbbVie, Sanofi, Regeneron, Bristol-Myers Squibb, Novartis, UCB, AB2 Bio Ltd, Debiopharm